2013
DOI: 10.1111/ijn.12144
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of education programme for preventing constipation in women

Abstract: This study was performed to evaluate the efficiency of the education programme for prevention of constipation in women. This study was performed as a pre-test-posttest design. Thirty-five women were included who have constipation problem. Data were collected by questionnaire: Constipation Severity Instrument (CSI), Constipation Visual Analogue Scale (CVAS) and Bristol Stool Chart (BSC). Eight home visits were made for each of the women and they were followed up for 3 months. Participants received an individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 33 publications
1
17
0
13
Order By: Relevance
“…12,16,26,30 In a study conducted in women having constipation, 74.3% were found to have a sedentary lifestyle. 31 Consistent with the literature, the group of participants in our study who reported not exercising regularly had a higher mean constipation risk score. The results of a study by Sendir et al 16 indicated that the patients were in the moderate risk group with a mean CRAS score of 12.73±4.75.…”
supporting
confidence: 91%
“…12,16,26,30 In a study conducted in women having constipation, 74.3% were found to have a sedentary lifestyle. 31 Consistent with the literature, the group of participants in our study who reported not exercising regularly had a higher mean constipation risk score. The results of a study by Sendir et al 16 indicated that the patients were in the moderate risk group with a mean CRAS score of 12.73±4.75.…”
supporting
confidence: 91%
“…Constipation is an important symptom affecting postoperative healing, quality of life, comfort, respiratory and circulatory systems of the patients, and quality of nursing care in the postoperative period ( 1 , 3 , 10 - 12 ). Place of surgical intervention, type of anesthesia, trauma of intestines during the operation, duration of postoperative immobility, suppression of defecation feeling, use of bedpan, inability to protect privacy, inability of the patients to verbally express their discomfort , using opioids/non opioids analgesic, fluid intake and alterations in dietary habits are effective in bowel elimination in the early postoperative period ( 6 , 10 - 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the effect of fibers or increasing water intake as isolated measures are limited and have not shown to be effective other than in patients with low fiber and water intake in their diet. [1][2][3] For that reason, we have a low recommendation for isolated changes in fiber intake, but a strong recommendation for a general intervention in the conjunction of lifestyle modifications, including dietary advice, physical exercise, and defecation habits. 4,5 In patients with constipation associated with irritable bowel syndrome, the increment in bowel contents, both water and gases, induced by fibers may be poorly tolerated by these patients, probably related to the visceral hypersensitivity that characterizes this disorder.…”
Section: Responses To the Letter To The Editor By Brusciano Et Almentioning
confidence: 99%